Navigate Career Thriving AI Powered Courses Guidance Junction with Students Reviews - Mrunal Fattepurkar,; Ankita Shelake,; Namrata Jagtap,; Sakshi More,; Sabiya Tamboli,; K. I. Chouhan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This project introduces a Student Review System, a web-based platform enabling students to share reviews on courses, professors, and facilities, fostering a valuable knowledge base for academic decision-making. Recognizing the challenges students face in choosing career paths, the Navigate Career Thriving AI-Powered Courses Guidance Junction with Student Reviews extends this concept by integrating peer and expert insights, personalized recommendations, and a real-time chatbot. The platform supports review creation, editing, and categorized searches, ensuring transparency and easy access to relevant insights. A user authentication system maintains credibility by preventing misuse. The chatbot provides interactive support, answering queries and offering tailored guidance aligned with individual interests. Additionally, analytical tools empower administrators to monitor feedback trends and address improvement areas, fostering institutional growth. This comprehensive system combines peer feedback and AI-driven recommendations to help students make confident, informed academic and career decisions.
Keywords: Student Review System; career guidance; AI-powered recommendation; peer reviews; chatbot integration; educational improvement